Analysis of the effect of promoter type and skin pretreatment on antigen expression and antibody response after gene gun-based immunization - Vij, Rajesh (PLoS One, 2018)
Monoclonal antibodies (mAbs) have enabled numerous basic research discoveries and therapeutic approaches for many protein classes. However, there still exist a number of target classes, such as multi-pass membrane proteins, for which antibody discovery is difficult, due in part to lack of high quality, recombinant protein. Here we describe the impact of several parameters on antigen expression and the development of mAbs against human claudin 4 (CLDN4), a potential multi-indication cancer target. Using gene gun-based DNA delivery and bioluminescence imaging, we optimize promoter type by comparing expression profiles of four robust in vivo promoters. In addition, we observe that most vectors rapidly lose expression, ultimately reaching almost background levels by three days post-delivery. Recognizing this limitation, we next explored skin pretreatment strategies as an orthogonal method to further boost the efficiency of mAb generation. We show that SDS pretreatment can boost antigen expression, but fails to significantly increase mAb discovery efficiency. In contrast, we find that sandpaper pretreatment yields 5-fold more FACS(+) anti-CLDN4 hybridomas, without impacting antigen expression. Our findings coupled with other strategies to improve DNA immunizations should improve the success of mAb discovery against other challenging targets and enable the generation of critical research tools and therapeutic candidates.